The Effect of Withering Methods on Physicochemical and Sensory Properties of Liberica Coffee Leaf Tea (Coffea liberica) - Surhaini, Surhaini; Indriyani, Indriyani; Suseno, Rahayu; Rinaldi, Rinaldi; Jie, Ferry; Wazzan, Huda (Department of Technology of Agricultural product (THP) Jambi University, 2025)
This study aims to evaluate the effect of different withering methods on physicochemical and organoleptic properties of Liberica coffee leaf tea (Coffea liberica) and to identify the optimal treatment. The experiment was conducted using a Completely Randomized Design (CRD) with five withering treatments, including no withering, room temperature withering for 10 h, air withering for 10 h, oven withering at 60°C for 30 min, and steaming for 2 min, each with four replications. The observed parameters included powder moisture content, pH, color (L*, a*, b*), antioxidant activity, total phenols, total tannins, flavonoids, and sensory attributes, namely color, aroma, acidity, taste, aftertaste, and overall acceptance. The results showed that withering method significantly affected color, moisture content, antioxidant activity, total phenols, total tannins, flavonoids, and organoleptic attributes related to aftertaste and overall acceptance, while pH, aroma quality, acidity, and taste were not significantly affected. The non-withered sample demonstrated the highest antioxidant activity and total phenolic content. The room temperature withering for 10 h produced antioxidant activity (57.59%) that was not significantly different from the non-withered sample, but offered superior sensory performance. This treatment produced a dark orange (brownish) infusion with L* (45.75), a* (29.25), and b* (49.50), the highest overall hedonic acceptance (3.72), and the most preferred color (3.84). In conclusion, withering at room temperature for 10 h represents the optimal processing method for producing Liberica coffee leaf tea with a balanced combination of functional properties and consumer acceptability.